Fungsi Satuan Polisi Pamong Praja dalam Penegakan Kawasan Jalur Hijau di Kabupaten Klungkung - I Komang Subagiarta (Jurnal Konstruksi Hukum, 2020)
The Indonesian Civil Service Police Unit (Satpol PP) appears as an institution established by the government as a regional apparatus that its existence has a strategic position in the administration of regional government in order to create order, security, and obedience to local communities to regional regulations. Therefore, the function of the Satpol PP is to enforce regional regulations, one of which is the enforcement of local regulations regarding green line areas, but their implementation has encountered various obstacles. To help overcome this, a scientific study has a position to fill in the gap in the form of the absence of efforts to reveal the major function of Satpol PP and the legal obstacles to implementing its activities. To reveal this, the present study was designed using a normative legal research method design. Data were collected using a document study technique and analysed using a legal argumentation technique. The results showed that the function of SatPol PP in enforcing green line area regulations in Klungkung Regency is the functions of guidance, control function and supervision of the implementation of public order related to the green line area. The realisation of the SatPol PP function in enforcing the green line regulation has not been maximally executed because there are still several obstacles, such as the Klungkung Regency SatPol PP has not been able to take full action in enforcing the green line regulation law in the Klungkung Regency area, the lack of personnel carrying out structuring, the limited coaching and controlling activities, and lthe ack of public awareness of applicable regulations related to green line areas.